Analysis of insoluble proteins - Sarah Trimpin; Bill Brizzard (BioTechniques)
The analysis of insoluble proteins represents a major technical challenge for the field of proteomics. For example, membrane proteins are often insoluble in common solvents and represent 20–30% of the proteins encoded by the human genome. Chemical analysis on an individual basis is often required and is laborious and time consuming. This review presents an overview of methods for purification of expressed proteins using fusion tags as well as methods for analysis of insoluble proteins by mass spectrometry with a goal of achieving high-throughput analysis.